Integrating Islamic and Cultural Values through the Merdeka Curriculum: A Character-Based Educational Perspective. - Lutfi Nurwahid Lutfi; Mega Hadistia; Hasna Farida; Liah Tarlia (Institut Agama Islam Persis Bandung, 2024)
The preservation of cultural values through education is a vital strategy in maintaining national identity amidst globalization that threatens local wisdom. This study applies a qualitative approach through literature review to analyze the role of education in transmitting cultural values and shaping students' character. The findings indicate that education plays a strategic function not only in transferring cultural heritage but also in cultivating moral and spiritual values rooted in local traditions and religious teachings. Formal, non-formal, and informal education must synergize in this process. The Merdeka Curriculum offers significant opportunities for innovation in local culture-based learning. The role of the teacher as a value model is essential, as emphasized in the concept of ta'dib by Syed Muhammad Naquib al-Attas. By simultaneously strengthening character and cultural education, education can serve as a progressive and inclusive agent of cultural transformation